Packaging of High Power Semiconductor Lasers - Liu, Xingsheng. (Micro- and Opto-Electronic Materials, Structures, and Systems,, 2015)
This book introduces high power semiconductor laser packaging design.  The characteristics and challenges of the design and various packaging, processing, and testing techniques are detailed by the authors.  New technologies, in particular thermal technologies, current applications, and trends in high power semiconductor laser packaging are described at length and assessed.